Маркс и слаборазвитость - Валлерстайн, И. (Социология: теория, методы, маркетинг, 2008)
In this article, Wallerstein discusses the problem how the concept of the third world underdevelopment relates to the Marxian concept of capitalism and what implications the relations of these two have for the conceptualization of capitalist development and for the social sciences and social movements.